1985
DOI: 10.1083/jcb.100.1.86
|View full text |Cite
|
Sign up to set email alerts
|

A cellular binding site for the Mr 55,000 form of the human plasminogen activator, urokinase.

Abstract: The secretion of plasminogen activators has been implicated in the controlled extracellular proteolysis that accompanies cell migration and tissue remodeling. We found that the human plasminogen activator urokinase (Uk) (Mr 55,000 form) binds rapidly, specifically, and with high affinity to fresh human blood monocytes and to cells of the monocyte line U937. Upon binding, Mr 55,000 Uk was observed to confer high plasminogen activator activity to the cells. Binding of the enzyme did not require a functional cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
365
1
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 693 publications
(390 citation statements)
references
References 37 publications
19
365
1
5
Order By: Relevance
“…11,12 uPAR is expressed by a wide range of immune cells whereas suPAR can be detected in different body fluids, including serum and plasma. [11][12][13][14][15][16][17] Cell-surface uPAR expression is up-regulated upon stimulation with growth factors and cytokines such as interleukin-1β and tumor necrosis factor. 18,19 The full length suPAR shed from the cell surface contains three domains (DI-III), and suPAR can occur in different cleaved forms consisting of only DI or DII-III, with partly divergent biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 uPAR is expressed by a wide range of immune cells whereas suPAR can be detected in different body fluids, including serum and plasma. [11][12][13][14][15][16][17] Cell-surface uPAR expression is up-regulated upon stimulation with growth factors and cytokines such as interleukin-1β and tumor necrosis factor. 18,19 The full length suPAR shed from the cell surface contains three domains (DI-III), and suPAR can occur in different cleaved forms consisting of only DI or DII-III, with partly divergent biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Urokinase can bind speci®cally and with high a nity (K D 90.5 nM) to a 45 ± 60 kDa heavily glycosylated cell surface receptor (u-PAR) (Stoppelli et al, 1986;Vassalli et al, 1985). The receptor is comprised of three similar repeats approximately 90 residues each Riittinen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that urokinase can bind to a 55 ± 60 kDa heavily glycosylated, disul®de linked, cell surface receptor (u-PAR) speci®cally and with high a nity (K D^0 .5 nM) (Stoppelli et al, 1986;Vassalli et al, 1985). This receptor is comprised of three similar repeats approximately 90 residues each Riittinen et al, 1996) the ®rst of which is required for the binding of urokinase and the last which is anchored to the cell membrane via a glycosyl-phosphatidylinositol chain .…”
Section: Introductionmentioning
confidence: 99%